The metabolism of lipoprotein (a): an ever-evolving story - Gissette Reyes-Soffer; Henry N. Ginsberg; Rajasekhar Ramakrishnan (Journal of Lipid Research, 2017)
Lipoprotein (a) [Lp(a)] is characterized by apolipoprotein (a) [apo(a)] covalently bound to apolipoprotein B 100. It was described in human plasma by Berg et al. in 1963 and the gene encoding apo(a) (LPA) was cloned in 1987 by Lawn and colleagues. Epidemiologic and genetic studies demonstrate that increases in Lp(a) plasma levels increase the risk of atherosclerotic cardiovascular disease. Novel Lp(a) lowering treatments highlight the need to understand the regulation of plasma levels of this atherogenic lipoprotein. Despite years of research, significant uncertainty remains about the assembly, secretion, and clearance of Lp(a). Specifically, there is ongoing controversy about where apo(a) and apoB-100 bind to form Lp(a); which apoB-100 lipoproteins bind to apo(a) to create Lp(a); whether binding of apo(a) is reversible, allowing apo(a) to bind to more than one apoB-100 lipoprotein during its lifespan in the circulation; and how Lp(a) or apo(a) leave the circulation. In this review, we highlight past and recent data from stable isotope studies of Lp(a) metabolism, highlighting the critical metabolic uncertainties that exist. We present kinetic models to describe results of published studies using stable isotopes and suggest what future studies are required to improve our understanding of Lp(a) metabolism.